Analisis Unsur Semiotika Penggunaan Bambu pada Masyarakat Etnik Mandar - Abdul Asis; Muhammad Firman Halip (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2020)
The Mandar tribe is one of the tribes in the province of West Sulawesi which has various local wisdoms. The Sendana community as one of the communities in the land of Mandar calls the name bamboo Tarring, in Sendana Village there are many types of bamboo that are grown and deliberately planted by residents, with many types of bamboo there are some of the residents who do not know the name, type, and use as well as the special meaning in the bamboos they encounter. This research is expected to provide useful data information in supporting the science of bamboo plants, as well as a library material for related parties in the context of developing the potential and utilization of bamboo. This research is a qualitative research with an interpretive description approach. Furthermore, the research refers to a semiotic analysis study based on Ferdinand De Saussure's theory by looking at the markers (signified) and markers (signifier) contained in the arrangement of the use of bamboo. Data collection techniques will use a documentation and interview system. Based on the results of the semiotic analysis of the use of bamboo in every activity that is considered sacred and the use of bamboo as the main material for the holy prayer, including substances that form the body, human existence, worship, forming blood according to its function, the cycle of human life, the structure of the building (Gazebo), tourism Mandar.